Digitalisasi Pencatatan Keuangan Berbasis Fintech: Akurasi dan Efisiensi Pelaporan Keuangan UMKM - Inuzula, Lakharis; Ginting, Erika Fahmi; Andriyani, Suci (Journal of Business and Economics Research (JBE), 2025)
Many Micro, Small, and Medium Enterprises (MSMEs) still rely on manual financial record-keeping and lack a well-documented, standardised accounting system. This complicates their ability to generate accurate and reliable financial reports in accordance with accounting standards. Such a situation is crucial for decision-making and reporting to relevant stakeholders. These limitations also hinder business development and increase the risk of financial data errors. To address this issue, the focus is on developing an application based on AppSheet that enables MSMEs to create financial reports in a practical, efficient manner, and in compliance with standards, without the need for coding expertise. This research employs a quantitative descriptive approach aimed at explaining the process of financial report preparation and assessing the effectiveness of the application in the context of MSMEs.Field research methods are essential for direct engagement with MSME practitioners, allowing for an understanding of their needs and the challenges they face in financial record-keeping, as well as the obstacles to digitalisation. The research approach utilised is descriptive quantitative, involving field studies and literature reviews, with stages that include literature review, application design, observation, data collection, testing, and financial report preparation.This application is expected to enhance accuracy, efficiency, and practicality in the financial record-keeping processes of MSMEs, while also facilitating their compliance with applicable financial reporting standards. The use of this technology is aimed at supporting MSMEs in improving the quality of financial management and ensuring the sustainability of their businesses.